THE EFFECT OF USING PICTURE WORD INDUCTIVE MODEL ON TEACHING DESCRIPTIVE TEXT WRITING - Suraya, Devi; Novita, Dewi; Fergina, Ana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The use of PWIM emphasized more on how students recognized the words by looking at the pictures teacher provided. The purpose of this research was to know the effect of using Picture Word Inductive Model on teaching descriptive text writing on the tenth- grade students of SMA Negeri 2 Sungai Raya, Kubu Raya. This research used quasi-experimental research pretest-posttest non-equivalent group design. The samples of this research were 20 students for experimental group and 20 students for control group. The use of Picture Word Inductive Model had an effect on teaching descriptive text writing. The effect size for the treatment was considered as strong, under the t-test the difference of the interval was significant. It is suggested that teacher uses PWIM as the alternative technique in teaching descriptive text.   Keywords: Writing, Picture Word Inductive Model, quasi-experimental research Abstrak: Penggunaan teknik PWIM lebih menekankan bagaimana murid mangenali kata dengan melihat gambar yang telah guru sediakan. Penelitian ini bertujuan untuk mengetahui efek dari Picture Word Inductive Model terhadap pengajaran penulisan deskriptif teks di kelas X SMA Negeri 2 Sungai Raya Kubu Raya. Metode penelitian yang digunakan adalah quasi experiment dengan rancangan penelitian pretest-posttest non-equivalent group design. Sampel penelitian ini adalah 20 siswa untuk kelas experiment dan 20 siswa untuk kelas kontrol. Penggunaan PWIM berdampak pada pengajaran descriptive teks writing, efek dari perlakuan dianggap mempunyai efek yang kuat dan adanya perbedaan yang signifikan dari t-test. PWIM disarankan untuk digunakan oleh guru bahasa inggris untuk mendapatkan skor lebih baik dan sebagai teknik alternative untuk mangajar writing.   Kata Kunci : Menulis, Picture Word Inductive Model, penelitian quasi-     experimental